Aplicação do delineamento experimental das faces centradas para simular o transporte de material em suspensão e dissolvido em superfície impermeável sob chuva artificial - Pessoti, Bruna Peterson Luque (2018)
Increased cities and population growth have caused changes in the environment, with major changes in natural systems, modifying the hydrological processes involved, such as surface runoff and water quality. The study of the surface runoff and transport of pollutants is of big importance, as it helps in the prevention of environmental impacts, aiding in planning to be carried out by the public authorities. The objective of this work was to study the transport of suspended material (sand) and dissolved material (sodium chloride) in relation to the change of three independent variables, slope, precipitation intensity and material position, using a rainfall simulator and surface in the laboratory. In the work was done an experimental design (Face Centered Design), in which different scenarios were proposed to perform the experiments. Hydrographs and polutograms were obtained for the different scenarios, where the influence of the independent variables on the dependent variables (transport time, peak value, peak time and total mass) was evaluated. With data analysis, it was possible to notice that the presence of suspended or dissolved material on the surface did not influence the flow, however, it was observed a strong influence of the precipitation slope and intensity, where the scenarios of greater slopes and intensities, produced higher volume drained From the data of polutogramas it was possible to perceive great difference of the transport for the two types of materials studied. The dissolved material has faster transport time, higher peak values, faster peak times and even higher total mass transported when compared to suspended material. In the suspended material, it was possible to observe the effect of slope and position of the material on all the dependent variables studied, as well as the quadratic effect of the slope for the peak value, its respective time and total mass. The precipitation intensity for the suspended material was significant for all the dependent variables studied except for the peak time. For the obtained results of dissolved material we noticed an effect of the slope and position of the material for all the dependent variables studied, as well as the quadratic effect of the slope for the transport time and total mass transported, whereas the intensity of precipitation influences only for the transport time.